Improved Learning Outcomes of Social Science Lessons Through Self Organized Learning Environments (SOLE) - Nurhidayah, Dian Yuliana (Universitas Sebelas Maret, 2022)
This research aims to improve the learning outcomes of fourth grade students at SD N 01 Gondangmanis in 2021/2022 in social studies learning about economic activities and types of work by applying the Self Organized Learning Environments (SOLE) learning model. This research is a classroom action research that goes through four stages, namely planning, action, observation, and reflection. The results of the research show that the application of the SOLE learning model can improve student learning outcomes in the material of economic activities and types of work in class IV students at SDN 01 Gondangmanis in 2021/2022. In the pre-action results, only 2 or 25% of students managed to obtain a complete score. Minimum (KKM = 70) with an average value of 63.75. The action taken is the application of the Self Organized Learning Environments (SOLE) learning model. In the first cycle, the results obtained were 5 or 67.5% of the 8 students who managed to get a complete score with an average score of 70.62. Whereas in the second cycle the results obtained were 7 or 87.5% of the 8 students who succeeded in obtaining a complete score with an average score of 84.37.